Frequency of Xerosis in Children Presenting with Chronic Pruritus - Naz, Shahida; Riaz, Sarah; Khan, farooq Azam; Zahoor, Hina; Sohail, Muhammad; Nadeem, Arshad (Journal of Gandhara Medical and Dental Science, 2021)
OBJECTIVES: To determine the frequency of Xerosis in children presenting with chronic pruritus to Hayatabad Medical Complex Peshawar, Khyber Pakhtunkhwa, Pakistan and compare it with national and international data. METHODOLOGY: This was a cross sectional study, carried out in the Department of Dermatology, Hayat Abad MedicalComplex Peshawar from 24th May 2020 till 24th November 2020. All patients of either gender with age range up to 13 years, presenting with chronic pruritus were enrolled for this study.All the findings were recorded on a preformed proforma and results were compiled and tabulated. RESULTS: Out of 136 patients presenting with chronic pruritus, 75 were male (55.1%) and 61 (44.9%) were female. 85 (62.5%) patients were having dry skin (Xerosis) while 37.5% were having normal skin. CONCLUSION: Xerosis is a common and under diagnosed skin condition commonly associated with chronic pruritus and screening all children for Xerosis is simple measures to improve quality of life of affected children.